A The Panopticon in Action: Analyzing the Impact of Societal Expectations on the Protagonist of Paulo Coelho's "Veronika Decides to Die" - Isha Banaras (Scholar Insight Journal, 2023)
Human beings think of their actions and decisions to be an outcome of independent thinking and an expression of human agency, however, the reality is far too bitter. An individual's ideas are directly or indirectly influenced and controlled by the accepted discourse in society, which is an act of conformity.  Human beings consider their daily actions and ideas, the outcome of their independent thinking and acts of human agency. Driven by this tendency to conformity, individuals do not think of their actions as being influenced and manipulated by some other factor. Micheal Focault explored this dilemma in his book “Discipline and Punishment.” He explained the existence of such influencing structures that act as a gaze to direct others' actions. Utilizing this concept propounded by Focault, this research paper explores the themes of normative conformity in Paulo Coelho's "Veronika Decides to Die(1998)." It highlights how the protagonist of the novel attempts to revolt against the influencing power, however towards the end she also submits to the societal codes. The study aims to portray society as an institution while also describing the effects of normative conformity on Veronika in the novel. This paper shows that an individual follows a routine without realizing it; during this, his soul gets imprisoned, and doing the same act is considered normal. Society’s capacity to accept unconventional practices and ideas is essential for cultural growth.
Keywords: Normative conformity; Panopticon; Paulo Coelho; Micheal Foucault